1988
DOI: 10.1017/s0266462300003202
|View full text |Cite
|
Sign up to set email alerts
|

The State of the Art Versus the State of the Science: The Diffusion of New Medical Technologies into Practice

Abstract: This paper offers a theory to explain the diffusion of new medical technologies into local practice. Based on several hundred interviews with community hospital physicians, it anchors technology decisions in the norms and relationships of local practice. Physician descriptions of their use of different types of assessment information provide insight into the way in which local consenses on appropriate practice are formed, guide behavior, and change. To understand new technology adoption, it is necessary to (a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
8

Year Published

1991
1991
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(120 citation statements)
references
References 32 publications
3
103
0
8
Order By: Relevance
“…This is consistent with previous research that has found that local opinion leaders can influence change in the clinical practices of health professionals (Lomas 1991). It is suggested that such people may perform a "sanctioning function" for new procedures (Greer 1988), or impact on peer attitudes and beliefs (Mittman et al 1992).…”
Section: Cultural and Attitudinal Changessupporting
confidence: 90%
“…This is consistent with previous research that has found that local opinion leaders can influence change in the clinical practices of health professionals (Lomas 1991). It is suggested that such people may perform a "sanctioning function" for new procedures (Greer 1988), or impact on peer attitudes and beliefs (Mittman et al 1992).…”
Section: Cultural and Attitudinal Changessupporting
confidence: 90%
“…Although this approach satisfies the apparent role of the consensus process in synthesizing research information, it can conflict with the credibility to a community practitioner audience. In other work, researchers found significant resistance among community practition ers to "ivory tower" medicine as espoused by academic consensus panels (35,56). There is no obvious balance between these potentially competing de mands on consensus group membership.…”
Section: Lomasmentioning
confidence: 98%
“…New medical technologies are frequently introduced by pharmaceutical companies and medical device manufacturers, sometimes with involvement of physicians. However, when a technology is introduced, the timing of its adoption and the extent to which it is used may vary across those who utilize it (Freiman 1985;Greer 1988;Escarce et al 1995;Escarce 1996;Hirth, Fendrick, and Chernew 1996;Burt and Sisk 2005;Gans et al 2005). It has been argued that the heterogeneity in the timing and extent of adoption may be linked to peer relations and that the nature of professional ties may lead to either underutilization or overutilization of new technologies from a welfare perspective (Escarce 1996).…”
Section: Introductionmentioning
confidence: 99%